Effect of Sowing Time and Nutrient Management on Physiological Parameters of Wheat - Bhayal, Lalita; Kewat, M. L.; Aakash,; Jha, A. K.; Bhayal, Divya; Badkul, Anamika Jain (International Journal of Economic Plants, 2022)
A study was undertaken to evaluate the impact of soil application of spent mushroom substrate (SMS) and farm yard manure (FYM) enriched with T. harzianum on pre-emergency damping off (PED) and post-emergence damping off (POED) in chilli and tomato seedlings in nursery beds containing naturally infested soil with Pythium aphanidermatum and Rhizoctonia solani in the experimental field area of Department of Plant Pathology, CCSHAU Hisar during 2018-19, 2019-20and 2020-21.The observations on disease incidence (%) were recorded up to 30 days after germination. A control without soil amendment was also maintained. The maximum damping off was at 22.5, 23.4 and 22.9% in controland minimum at 15.7, 15.8 and 16.6% during 2018–19, 2019–20, 2020–21, respectively in chilliwhen SMS enriched with T. harzianum was applied. The mean of damping off disease incidence was minimum at 16.0% when SMS enriched with T. harzianum was applied and maximum at 22.9% in control. The maximum damping off was at 18.1, 19.4 and 18.7% in control and minimum at 12.2, 12.6 and 14.8% during 2018–19, 2019–20, 2020–21, respectively in tomato when SMS enriched with T. harzianum was applied. The mean of disease incidence (%) was minimum at 13.2% when SMS enriched with T. harzianum was applied and maximum at 18.7% in control.